Response to “Practice what you preach: Ensuring scientific spheres integrate Indigenous Peoples’ and Local Communities’ rights and agency too” by Lopez-Maldonado - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; David García-del-Amo; Natalia Hanazaki; Ana C. Luz; Pamela McElwee; Vicky J. Meretsky; Zsolt Molnár; Isabel Ruiz-Mallén; et al. (Ambio, 2022)

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

Learning from Conservation Planning for the U.S. National Wildlife Refuges - VICKY J. MERETSKY; ROBERT L. FISCHMAN (Conservation Biology, 2014)
The U.S. National Wildlife Refuge System has nearly completed its first round of unit‐level, comprehensive conservation plans (CCPs) and will soon begin required revisions. Laws and policies governing refuge planning emphasize ecological integrity, landscape‐scale conservation, and adaptive management. We evaluated 185 CCPs completed during 2005–2011, which cover 324 of 555 national wildlife refuges. We reviewed CCP prescriptions addressing 5 common conservation issues (habitat and game, nongame, imperiled, and invasive species) and 3 specialized topics (landscape‐scale conservation, climate change, and environmental quality). Common conservation issues received prescriptions in >90% of CCPs. Specialized topics received more variable treatment. Prescriptions for aquatic connectivity, water quantity, and climate‐change impacts increased over the study period. Except for climate change, direct actions were the most common type of management prescription, followed by plans or studies. Most CCPs stated a commitment to adaptive management and prescribed monitoring for common conservation objectives; other aspects of planning for adaptive management were often lacking, despite strong support for adaptive management in the conservation planning literature. To better address refuge‐specific threats, we recommend that revised plans explicitly match identified refuge issues with prescriptions, particularly for under‐represented concerns such as novel pests and pathogens. We recommend incorporating triggers into monitoring frameworks and specifying actions that will occur when threshold values are reached to improve support for adaptive management. Revised CCPs should better reflect work that refuges already undertake to extend conservation objectives beyond their borders and better engage with regional conservation efforts to continue this work. More thorough landscape‐scale threat assessments and explicit prioritization of planned actions would further improve conservation effectiveness. Excellent examples of all recommended practices exist within the CCPs we examined; sharing best planning practices would improve planning efficiency within the refuge system. Aprendiendo de la Planeación de la Conservación para los Refugios Nacionales de Vida Silvestre de EUA

Motivations Influencing the Adoption of Conservation Easements - JAMES R. FARMER; DOUG KNAPP; VICKY J. MERETSKY; CHARLES CHANCELLOR; BURNELL C. FISCHER (Conservation Biology, 2011)
The use of conservation easements as a conservation mechanism for private land has increased greatly in the past decade; conservation easements now protect over 15 million ha across the United States from residential and commercial development. We used a mailed survey and in‐depth telephone interviews to determine factors that motivate private landowners in Iowa, Illinois, Michigan, Ohio, and Wisconsin (U.S.A.) to place conservation easements on their properties. The mailed survey asked about characteristics of landowners, their properties, and their opinions on 9 factors related to the decision to place an easement. A follow‐up telephone interview was completed with 19 mail‐survey participants to gain an in‐depth understanding of the action and to triangulate the results with the questionnaire. Place attachment, which is a measure of personal connection to a location or property, was the greatest motivation for implementation of an easement. Results of a principal components analysis suggested contributing to the public good underlaid several of the strong motivational factors for participation. Financial reasons were the lowest ranked motivational factor; however, financial concerns may facilitate placement of an easement that would otherwise not be realized. We believe that our results may be transferable to places where land protected by easements is not dominated by traditional farming (row crops, pastures, and hay), timber harvesting, or nonextractive uses (e.g., habitat for wild animals, recreation, and protection of ecosystem services).

Demography of the California Condor: Implications for Reestablishment - Vicky J. Meretsky; Noel F. R. Snyder; Steven R. Beissinger; David A. Clendenen; James W. Wiley (Conservation Biology, 2000)
The remnant wild population of California Condors ( Gymnogyps californianus ) of the 1980s exhibited a rapid population decline caused by high mortality rates among adult and immature birds. The most prominent mortality factor was lead poisoning resulting from ingestion of bullet fragments in carcasses. Successful captive breeding has allowed many birds to be released to the wild since 1992, based originally on an assumption that exposure to lead could be prevented by food subsidy. The mortality of released birds, however, has generally exceeded levels needed for population stability calculated from simple population models. Collision with overhead wires was the most frequent cause of death in releases before 1994. Lead poisoning again surfaced as a problem starting in 1997 as older birds began feeding on carcasses outside the subsidy program. Although poisonings have been treated successfully by chelation therapy in recaptured birds, food subsidy is proving an ineffective solution to lead exposure. The best long‐term solution appears to be either the creation of large reserves where hunting is prohibited or the restriction of hunting to nontoxic ammunition in release areas. Until sources of lead contamination are effectively countered, releases cannot be expected to result in viable populations. In addition, problems involving human‐oriented behavior have resulted in the permanent removal of many released birds from the wild. The most promising reduction in human‐oriented behavior has been achieved in one release of aversively conditioned, parent‐reared birds. Rigorous evaluation of the factors reducing attraction to humans and human structures has been hampered by confounding of techniques in releases. Behavioral problems could be more quickly overcome by adoption of a comprehensive experimental approach.

Balancing Endangered Species and Ecosystems: A Case Study of Adaptive Management in Grand Canyon - Vicky J. Meretsky (Environmental Management, 2000)